Pengaruh Inovasi Produk Dan Kualitas Produk Terhadap Minat Beli Ulang Pada UKM Mie Setan Kota Malang - Paramita Gita Prameswari; Farida Akbarina (Jurnal Ekonomi dan Bisnis Digital, 2025)
Economic growth is inseparable from the development of the competitiveness of a business within the company. The progress of a business will have a very positive impact on the economic recovery. The rapid development of the competitiveness of a business is in line with the increasing primary and secondary needs that continue to increase. It is marked in the global era of the Food and Beverage (F&B) industry in Indonesia by the dynamics that have grown rapidly in recent decades. This study aimed to examine the effect of product innovation and product quality partially and simultaneously on the repurchase interest in Mie Setan Malang City. This research was a quantitative study with variables of product innovation, product quality and repurchase interest. This study used questionnaire and observation data collection techniques. With the purposive sampling technique, 100 respondents were obtained from the customers of UMKM Mie Setan Malang City. The data analyses used were multiple linear regression and hypothesis testing. The results of partial hypothesis testing, product innovation variables have a positive and significant effect on repurchase interest. The results of simultaneous hypothesis testing showed that the variables of product innovation and product quality have a positive and significant effect on repurchase interest. From the results of this study, it is concluded that there is an influence between product innovation and product quality on repurchase interest in UMKM Mie Setan Malang City. Therefore, it is recommended that Mie Setan Malang City need to focus on the menu offered and improve the quality of its products.